Phenomenological Analysis of Organization-Based Moderate Islamic Education in Madura - Muh. Azkar; Maimun; Abdul Azis (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
This research aims to understand how Aswaja teachers interpret ikhtilaf in NU-based Aswaja subjects at NU-based Islamic educational institutions in Madura. This research uses a phenomenological approach with data collection techniques through in-depth interviews, observations, and documentation. Phenomenological analysis is used to explore teachers' subjective experiences, then combined with theoretical analysis that refers to Max Weber's theory of social action, specifically the concept  of verstehen and the rationality of value (wertrational), to understand the meaning behind their pedagogical actions. The findings of the study show that ikhtilaf has three main meanings. First, as a general and flexible sunnah practice. Second, as mercy, which is seen as a manifestation of Allah's love for His people. Third, as an organizational identity that gains cultural, structural, and theological legitimacy. This meaning is formed through the process of primary socialization in the family and ngaji teachers, as well as secondary socialization in Islamic boarding schools and the social environment of NU-an. From the perspective of social action, this meaning represents the rationality of values based on obedience to scholars and religious postulates. Therefore, when faced with organizations with different views, Aswaja teachers show an open attitude as long as their religious practices are not disturbed or discredited.